The pH-solubility profiles of levofloxacin hemihydrate and ciprofloxacin lactate - Isadiartuti, Dewi; Sari, Retno; Retnowati, Dini; Yanti, Risma Dama; Gunawan, Violyta Ade; Yudiswara, Oki (Pharmacy Education, 2024)
Background: Levofloxacin and ciprofloxacin are popular fluoroquinolone antibiotics that offer diverse therapeutic potentials due to their broad-spectrum activity. Levofloxacin and ciprofloxacin, commonly used as active pharmaceutical ingredients (API) in parenteral form, are amphoteric compounds with pH-sensitive solubility. This characteristic may affect the safety and efficacy of levofloxacin and ciprofloxacin, especially in the parenteral dosage forms. Objective: This study aims to assess the solubility of levofloxacin hemihydrate and ciprofloxacin lactate in buffer solutions with pH ranging from 3.0 to 8.0. Method: The solubility test was conducted in a 0.02 M buffer pH solution featuring an ionic strength (µ) of 0.2. After weighing several API samples, ultrasonication was carried out for 15 minutes. The solution was agitated at 150 rpm and 30 ± 0.5°C until it reached equilibrium (four hours). The API concentration was observed using a UV-Vis spectrophotometer. Result: The solubility ranges of levofloxacin hemihydrate and ciprofloxacin lactate were 44.39 to 70.66 mg/mL and 0.23 to 243.00 mg/mL, respectively, within the experimental pH range. Conclusion: This study concluded that levofloxacin hemihydrate and ciprofloxacin lactate solubility were increased due to decreasing pH medium.